The IGF receptor as anticancer treatment target. - Macaulay, V (2004)
The type 1 insulin-like growth factor receptor (IGF-1R) is overexpressed by many tumours and mediates proliferation, motility and apoptosis protection. Tumour growth and metastasis can be blocked by agents that inhibit IGF-1R expression or function, suggesting the IGF-1R as a promising treatment target. We showed that antisense-IGF-1R expression in melanoma cells leads to enhanced radiosensitivity and impaired activation of ATM, required for DNA double-strand break repair. Antisense and dominant negative strategies also enhance tumour cell chemosensitivity, and remarkably, immune protection can be induced by tumour cells killed in vivo by IGF-1R-antisense. However, antisense agents cause only modest IGF1R down-regulation, and can affect the insulin receptor. Specificity is an important issue for development of both kinase inhibitors and molecular reagents. Using an array-based screen to identify accessible regions of IGF1R mRNA, we designed small interfering RNAs (siRNAs) that induce potent IGF1R gene silencing without affecting the insulin receptor. These siRNAs block IGF signalling, enhance radio- and chemosensitivity, and show genuine therapeutic potential. The clinical efficacy of IGF-1R targeting will be determined by key factors including the role of the receptor in established tumours, the potency of inhibition achieved in vivo, and the extent to which other signalling pathways compensate for IGF-1R loss.